Pilot fatigue survey: A study of the mutual influence among fatigue factors in the “work” dimension - Jun-Ya, Sun; Rui-Shan, Sun (Frontiers in Public Health, 2023)
Background: Fatigue risk management for pilots has been paid more and more attention. The existing fatigue management systems have detailed descriptions of the factors and the mutual influence among the factors that affecting the dimension of “sleep”, one of the most important causes of fatigue. However, the analysis of the influencing factors of the “work” dimension of fatigue causes is not very detailed and perfect, especially the exploration of the mutual influence among many fatigue influencing factors in the “work” dimension. Objective: The purpose of this study is to explore the mutual influence among fatigue influencing factors related to the “work” dimension in the analysis of pilot fatigue causes. Methods: This study designed a questionnaire on the dimension of “work” in the causes of pilot fatigue, and collected a total of 270 feedback data from international flight pilots. Based on the questionnaires and data, descriptive statistical analysis, exploratory factor analysis and confirmatory factor analysis were carried out to explore the influencing factors and their mutual influence of the “work” dimension of pilot fatigue. Results: There is a strong mutual influence relationship among the fatigue causes of long-haul flight pilots - working status, working conditions and working schedules in the dimension of “work”. The workload only has a strong correlation with the working schedules, and the interaction relationship with the working status or working conditions is weak. Conclusion：This study analyzes the mutual influence among the influencing factors of the “work” dimension of pilot fatigue, expecting to provide empirical data for pilot fatigue risk management, and to provide help for the improvement of the fatigue risk management system.